2016
DOI: 10.1111/jam.12999
|View full text |Cite
|
Sign up to set email alerts
|

Zebra mussel as a new tool to show evidence of freshwater contamination by waterborneToxoplasma gondii

Abstract: This study shows that transplanted zebra mussels could be used as biosamplers to reveal contamination of freshwater systems by T. gondii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
(110 reference statements)
0
25
0
1
Order By: Relevance
“…Laboratory studies have shown that marine and freshwater bivalves can concentrate waterborne protozoan parasites (18)(19)(20). Consistent with this, some studies have reported the detection of T. gondii oocysts in different marine (12,(21)(22)(23) or continental (24) bivalves, allowing the study of a large spatial scale (freshwater-seawater continuum).…”
Section: Introductionmentioning
confidence: 73%
“…Laboratory studies have shown that marine and freshwater bivalves can concentrate waterborne protozoan parasites (18)(19)(20). Consistent with this, some studies have reported the detection of T. gondii oocysts in different marine (12,(21)(22)(23) or continental (24) bivalves, allowing the study of a large spatial scale (freshwater-seawater continuum).…”
Section: Introductionmentioning
confidence: 73%
“…In spring, T. gondii was detected upstream of one WWTP. These results highlight the interest to use D. polymorpha caged as a new effective tool in sanitary biomonitoring of water bodies [28].…”
Section: Protozoa Pathogensmentioning
confidence: 77%
“…In fact, the caging of individuals from the same population (and a fortiori the same species) in different sites allows (i) to limit or avoid influence of intrinsic parameters and (ii) to expose organisms for a time-limited period, so recent contamination can be detected. As for contamination level and/or biological effects associated, several studies had underlined the interest of the active biomonitoring approach using the zebra mussel, D. polymorpha [28,52,53,77,78]. In the purpose of improving the ecological relevance of biomarkers as early-warning responses, many studies proposed to apply a multi-biomarkers approach considering physiological processes particularly those implied to maintain an individual and/or its population (e.g., reproduction, energy, and immunity) as indicated in part 3 of this chapter.…”
Section: Interest Of D Polymorpha In Aquatic Biomonitoring Frameworkmentioning
confidence: 99%
“…It is therefore necessary to define the effects of protozoa on zebra mussel health. Dreissena polymorpha was chosen for this experiment for several reasons: (i) it is a sentinel freshwater species frequently used in ecotoxicological studies, (ii) it can accumulate these protozoa, whether in laboratory studies or in the field (Graczyk et al ., ; Palos‐Ladeiro et al ., ; Kerambrun et al ., ) and (iii), although it is a paratenic host for the three protozoa mentioned above, their consequences on biological responses, especially on the immune system, are still unknown (Palos‐Ladeiro et al ., ). The bioaccumulation of protozoa by mussels is organ‐dependent, mainly observed in the mantle and the haemolymph compartments (Palos‐Ladeiro et al ., ).…”
Section: Haemocyte Mortality and Flow Cytometry Parameters After Ex Vmentioning
confidence: 99%